Perceptions and predictors of organizational justice among healthcare professionals in academic hospitals in South-Eastern Nigeria - Nwanneka Chidinma Ghasi; Daniel Chukwuemeka Ogbuabor; Vincent Aghaegbunam Onodugo (BMC, 2020)
Abstract Background Research on organizational justice in hospitals in African countries are limited despite being important for workforce performance and hospital operational efficiency. This paper investigated perceptions and predictors of organizational justice among health professionals in academic hospitals in South-east Nigeria. Methods The study was conducted in two teaching hospitals in Enugu State, South-east Nigeria using mixed-methods design. Randomly sampled 360 health professionals (doctors = 105, nurses = 200 and allied health professionals, AHPs = 55) completed an organizational justice scale. Additionally, semi-structured, in-depth interview with purposively selected 18 health professionals were conducted. Univariate and bivariate statistics and multivariable linear regression were used to analyze quantitative data. Statistical significance was set at alpha 0.05 level. Qualitative data were analyzed thematically using NVivo 11 software. Results The findings revealed moderate to high perception of different dimensions of organizational justice. Doctors showed the highest perception, whereas AHPs had the least perception. Among doctors, age and education predicted distributive justice (adjusted R2 = 22%); hospital ownership and education predicted procedural justice (adjusted R2 = 17%); and hospital ownership predicted interactional justice (adjusted R2 = 42%). Among nurses, age, gender and marital status predicted distributive justice (adjusted R2 = 41%); hospital ownership, age and gender predicted procedural justice (adjusted R2 = 28%); and hospital ownership, age, marital status and tenure predicted interactional justice (R2 = 35%). Among AHPs, marital status predicted distributive justice (adjusted R2 = 5%), while hospital ownership and tenure predicted interactional justice (adjusted R2 = 15%). Qualitative findings indicate that nurses and AHPs perceive as unfair, differences in pay, access to hospital resources, training, work schedule, participation in decision-making and enforcement of policies between doctors and other health professionals due to medical dominance. Overall, supervisors have a culture of limited information sharing with, and disrespectful treatment of, their junior colleagues. Conclusion Perceptions of organizational justice range from moderate to high and predictors vary among different healthcare professionals. Addressing specific socio-demographic factors that significantly influenced perceptions of organizational justice among different categories of health professionals and departure from physician-centered culture would improve perceptions of organizational justice among health professionals in Nigeria and similar settings.